Maturity Level of Fraud Risk Management in Tax Institutions in Indonesia - Ariyadi Teguh Wibawa; Agustinus Nicholas L Tobing (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to determine the maturity level of fraud risk management in the tax payer compliance supervision function at the head office level run by VW and the XYZ units. The Enterprise Anti-Fraud Maturity Assessment Model was implemented to provide a clear picture of conditions and effectiveness, as well as the existing gaps between the implementation and ideal conditions based on the principles of COSO Fraud Risk Management. The descriptive qualitative research uses a case study approach by collecting data from semi-structured interviews with 12 informants involved in risk management and fraud risks handling, then all documents are analyzed. As for the data analysis technique, content analysis is selected. The purpose of this study is to provide a tool for DGT (The Directorate General of Taxes) to determine the role and level of fraud risk management in the taxpayer compliance supervision function. The results which are at level 2 (initial) indicate that there is still a lot of room for improvement in order to achieve the desired maturity level target. DGT, especially the VW unit and XYZ unit, are suggested to immediately integrate fraud risk management with the existing anti-fraud programs and strengthen the role of the units involved in accordance with the COSO (Committee of Sponsoring Organizations) Fraud Risk Management principles.